2020
DOI: 10.1038/s41438-020-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of expression quantitative trait loci (eQTLs) reveals the regulatory architecture of gene expression variation in the storage roots of sweet potato

Abstract: Dissecting the genetic regulation of gene expression is critical for understanding phenotypic variation and species evolution. However, our understanding of the transcriptional variability in sweet potato remains limited. Here, we analyzed two publicly available datasets to explore the landscape of transcriptomic variations and its genetic basis in the storage roots of sweet potato. The comprehensive analysis identified a total of 724,438 high-confidence single nucleotide polymorphisms (SNPs) and 26,026 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 65 publications
3
37
0
Order By: Relevance
“…Sequencing data analysis was performed according to our previous studies [25,26]. High-quality clean reads for each sample were obtained from raw RNA-seq data by removing adaptor sequences and ambiguous nucleotides using Trimmomatic (version 0.34) [27] and then were mapped to the eggplant genome HQ-1315 [28] using STAR (version 2.7.1a) under the 2-pass mapping mode [29].…”
Section: Transcriptome Sequence Processing and Analysismentioning
confidence: 99%
“…Sequencing data analysis was performed according to our previous studies [25,26]. High-quality clean reads for each sample were obtained from raw RNA-seq data by removing adaptor sequences and ambiguous nucleotides using Trimmomatic (version 0.34) [27] and then were mapped to the eggplant genome HQ-1315 [28] using STAR (version 2.7.1a) under the 2-pass mapping mode [29].…”
Section: Transcriptome Sequence Processing and Analysismentioning
confidence: 99%
“…The anthocyanin synthesis in plants could also be regulated by visible light or be light independent. For instance, the roots of some potatoes (Liu et al, 2016;Vincenzo et al, 2014), sweet potatoes (Mano et al, 2007;Zhang et al, 2020), and carrots (Xu et al, 2019), the flesh of some apples (Chagné et al, 2013;Espley et al, 2007), kiwifruits (Wang et al, 2019), and plums (Niu et al, 2017) can accumulate abundant amounts of anthocyanins via the regulation of MYB transcription factors during their growth underground, or above the ground in the dark. After photosynthesis was interrupted, the anthocyanin synthesis was inhibited in turnip (Schneider & Stimson, 1971), corn (Kim et al, 2006), and Arabidopsis (Jeong et al, 2010).…”
mentioning
confidence: 99%
“…(Zhang et al. , 2020 ), and traits devised alternative ways to integrate phenotyping, transcriptomic, and GWA data to prioritize candidate genes. These studies demonstrated that combined approaches, when applied on large datasets in some cases already available in the literature, may effectively advance our understanding of the molecular mechanisms underlying complex traits and provide candidate genes to prioritize for validation and breeding.…”
Section: Discussionmentioning
confidence: 99%